2017
DOI: 10.1002/prp2.301
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of a mitochondrial-targeted coenzyme Q analog in high fat fed obese mice

Abstract: We recently reported that mitoquinone (mitoQ, 500 μmol/L) added to drinking water of C57BL/6J mice attenuated weight gain, decreased food intake, increased hypothalamic orexigenic gene expression, and mitigated oxidative stress when administered from the onset of high‐fat (HF) feeding. Here, we examined the effects of mitoQ on pre‐existing obesity in C57BL/6J mice first made obese by 107 days of HF feeding. In contrast to our preventative study, we found that already obese mice did not tolerate mitoQ at 500 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…As shown in Figure A and B, food intake was mildly but not significantly reduced in the mitoQ‐ compared to vehicle‐treated mice. Consistent with past reports by ourselves and others, water intake by the mitoQ‐treated mice was reduced (Figure C and D).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…As shown in Figure A and B, food intake was mildly but not significantly reduced in the mitoQ‐ compared to vehicle‐treated mice. Consistent with past reports by ourselves and others, water intake by the mitoQ‐treated mice was reduced (Figure C and D).…”
Section: Resultssupporting
confidence: 92%
“…Our current results are largely consistent with our past studies of the action of mitoQ on HF‐fed mice. In both this study and in past reports we found that mitoQ improved energy expenditure (based on gas respiratory exchange) and decreased food intake. However, in our past reports, unlike the present, the effect on whole body respiration was short of significance.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations